Sodium Alginate - Gelatin Cross-Linked Microspheres for Releasing Diltiazem Hcl - Tareq, Alarqam Z.; Hussein, Mohammed S. (Science Journal of University of Zakho, 2016)
Semi-interpenetrating polymer network (semi-IPN) microspheres of Sodium alginate (NaAlg) and Gelatin were prepared and cross-linked with glutaraldehyde by using emulsification/solvent-evaporation method to deliver Diltiazem HCl as a model of drug. Diltiazem HCl was successfully loaded into NaAlg-Gelatin microspheres in different ratios of NaAlg and Gelatin. The prepared microspheres were characterized by Fourier Transmission Infrared Microscopy (FT-IR) and Scanning Electron Microscope (SEM). The effects of different process parameters, like percentage of polymers, swelling behavior and in vitro drug release of microspheres in different phosphate buffer solutions pH (7.1and3.9) were studied. The models of kinetics of releasing drug were investigated by using different types of mechanisms (Zero-order, First order, Higuchi’s model and Hixson-Crowell model).
Keywords: drug delivery system; sodium alginate; gelatin; Semi-interpenetrating polymer network microspheres